Pauson–Khand reaction of fluorinated compounds - Escorihuela, Jorge; Sedgwick, Daniel M.; Llobat, Alberto; Medio-Simón, Mercedes; Barrio, Pablo; Fustero, Santos (Beilstein Journal of Organic Chemistry, 2020)
The Pauson–Khand reaction (PKR) is one of the key methods for the construction of cyclopentenone derivatives, which can in turn undergo diverse chemical transformations to yield more complex biologically active molecules. Despite the increasing availability of fluorinated building blocks and methodologies to incorporate fluorine in compounds with biological interest, there have been few significant advances focused on the fluoro-Pauson–Khand reaction, both in the inter- and intramolecular versions. Furthermore, the use of vinyl fluorides as olefinic counterparts had been completely overlooked. In this review, we collect the advances both on the stoichiometric and catalytic intermolecular and intramolecular fluoro-Pauson–Khand reaction, with special attention to the PKR of enynes containing a fluoride moiety.
Keywords: alkene; alkyne; enyne; fluorine; Pauson–Khand